2005
DOI: 10.1002/art.21066
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic exercise capacity in patients with juvenile‐onset idiopathic inflammatory myopathies

Abstract: Objective. To 1) report the feasibility of an "all-out" 30-second cycling exercise test (Wingate Anaerobic Exercise Test [WAnT]) in juvenile-onset idiopathic inflammatory myopathy (JIIM) patients, 2) describe the anaerobic exercise capacity in juvenile dermatomyositis patients, and 3) determine if the anaerobic exercise capacity could be related to disease duration or disease phase. Methods. Twenty patients (age 14.13 ؎ 5.4 years) with JIIM participated in this study. All patients were able to perform the WAnT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 29 publications
1
38
1
7
Order By: Relevance
“…Therefore, we reinforce the idea that a series of tests, rather than only MMT and/or handgrip, should be applied in either clinical setting or research to sensitively assess muscle function in chronic JDM patients, with the guidance of the recently proposed core set [37]. Previous studies have shown that JDM patients often experience decreased strength and aerobic and anaerobic capacity [4][5][6]. These data were further confirmed in a chronic cohort of JDM patients, in which we showed that a supervised physical activity program was able to improve muscle strength, aerobic conditioning, disease activity, and health-related quality of life in chronic JDM patients [10], indirectly suggesting that physical inactivity could be partially implicated in the symptoms observed in JDM.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, we reinforce the idea that a series of tests, rather than only MMT and/or handgrip, should be applied in either clinical setting or research to sensitively assess muscle function in chronic JDM patients, with the guidance of the recently proposed core set [37]. Previous studies have shown that JDM patients often experience decreased strength and aerobic and anaerobic capacity [4][5][6]. These data were further confirmed in a chronic cohort of JDM patients, in which we showed that a supervised physical activity program was able to improve muscle strength, aerobic conditioning, disease activity, and health-related quality of life in chronic JDM patients [10], indirectly suggesting that physical inactivity could be partially implicated in the symptoms observed in JDM.…”
Section: Discussionsupporting
confidence: 67%
“…JDM patients often show chronic illness, sequelae of the disease, and poorer health-related quality of life [3]. Furthermore, most patients experience decreased muscle function, poor aerobic conditioning, and limited exercise tolerance [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Children with IIMs are usually hypoactive leading to deconditioning and reduction in functional ability. Even when disease is well controlled, they still experience significant fatigue [127] and anaerobic-and aerobic exercise intolerance [128]. Moreover, decreased physical activity is known to be related with complications associated with a sedentary lifestyle including cardiovascular disease and obesity.…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…Polega on na przesunięciu ogólnego rzutu środka ciężkości przed zablokowane w wyproście stawy kolanowe. Dzięki temu mechanizmowi możliwe staje się utrzymanie równowagi oraz stabilnej postawy wyprostowanej, przy użyciu minimalnej siły dużych grup mięśniowych [11][12][13].…”
Section: Analiza Zaburzeń Narządu Ruchuunclassified